Rambutan is a potential future fruit - Karunakaran, G; Tripathi, P C; Sakthivel, T; Ravishankar, H; Sankar, V; Kumar, R Senthil; Ranganath, H R; Mala, BR Jayanthi (Indian Horticulture, 2019)
Mr C.F. Jacob, Belthangadi, Puttur, Karnataka, has diversified into rambutan, in a region favorable for arecanut, black pepper, rubber and banana. Beginning of his new innings started with planting of 2 acres of rambutan. His visit to CHES, Chettalli, and interaction with scientists about status of rambutan production technologies gave great confidence and helped to earn maximum price for rambutan fruits through his own farm outlets, thereby fetching fabulous profit. The success mantra inspired others with the passage of time and in a phased manner he increased his cultivation to six acres with two different age groups of trees. In this region which is known for plantation crops, rambutan orchard has became centre of attraction for all the growers.